Do livro à minissérie: diálogos entre a obra literária Vozes de Tchernóbil e a série televisiva Chernobyl - Brito, Isabel Santos (2021)
The relationship between literature and cinema, although highly studied, is enriched each year, as written works are transposed to audiovisual language, from films to series in online streaming services. Thus, there is always a new point to be observed and analyzed. A recent example of this kind of mediatic transposition was the adaptation of the book Voices from Chernobyl: the oral history of a nuclear disaster, originally published by Svetlana Aleksiévitch in 1996, to the HBO miniseries of five episodes Chernobyl, in 2019. The 2015 Nobel winner book brought to the television series the base for several characters who lived the Chernobyl nuclear accident closely. However different, both works came from the same point: the real events of 1986. After knowing what happened, the goal of this study is to analyze each work individually, to comprehend its elements and behavior to, then, compare them in order to understand how one starting point could create such different works. The analysis will approach the similarities and differences between them, and how the process of transposition from the accident occurred with each creation. Contributing to the study of the relationship between written and television works, this dissertation will be made through qualitative analysis, based on literature theory and cinema theory, converging into the comparison.